Improving replicator dynamic evolutionary game model for selecting optimal defense strategies - Jianming HUANG; Hengwei ZHANG (Tongxin xuebao)
In terms of the existence of strategy dependency in the same game group,network attack-defense evolutionary game model based on the improved replicator dynamics was constricted by introducing the intensity coefficient,which completed the method of calculating replicator dynamic rate.The improved replicator dynamic equation was adopted to solve the evolutionary equilibrium for the situation that both attack and defense have two optional strategies.The stability of the equilibrium points was analyzed by the local stability analysis method of Jacobian matrix,and the optimal defense strategies were obtained under different conditions.The results show that the strategy dependency between the players in the same group has a certain influence on the evolution of the game,both the incentive and the inhibition.Finally,the accuracy and validity of the model and method are verified by the experimental simulation,which provides a new theoretical support for solving the information security problems in the real.